Categorisation of the length of bowhead whales from British Arctic whaling records - Wilkinson, Jeremy; Veyssière, Gaëlle; Hughes, Nick; Ayre, Matthew; Murray, Maribeth; Headland, Robert; Charles, Ryan (Frontiers in Marine Science, 2023)
British whalers were the first and last from Europe to hunt bowhead whales (Balaena mysticetus) commercially from the Arctic whaling grounds of the Greenland Sea (East Greenland-Svalbard-Barents stock) and Davis Strait (East Canada-West Greenland stock). Thus, British Arctic whaling records are unique, as they include both the beginning and the final story of the near extirpation of the species from these waters. By consolidating, cross-checking, and updating the work of numerous colleagues over the years, a database of over 11,000 individual records of British whaling voyages to these grounds between 1725 and 1913 has been established. Using conversion algorithms, it has been possible to derive statistically robust information on the length of the bowheads caught from the amount of oil they yielded. Translating oil yield to whale length is an important step as oil yield is one of the most common parameters documented within historical whaling records. Analysis suggests the length of whales caught at these two whaling grounds, Greenland Sea and Davis Strait, were different. A higher proportion within the East Greenland-Svalbard-Barents stock, taken from the Greenland Sea grounds, measured less than 12.5m (classed as juveniles), whilst the East Canada-West Greenland stock, taken from Davis Strait grounds, were skewed towards larger whales, 13 to 14 m long (classed as sexually mature). Furthermore, there was clear evidence that a shift in the distribution of whale length occurred when the whalers extended their hunting grounds to encompass additional regions within the Greenland Sea and Davis Strait in 1814 and 1817 respectively. Prior to expansion, we find that that the vast majority (85%) of the East Canada-West Greenland stock were of the length that are classified as sexually mature (>13.0 m), whereas only 39% of East Greenland-Svalbard-Barents stock taken were of this size. After the enlargement of the whaling grounds, the length distribution shifted with a reduction to 50% of the East Canada-West Greenland stock and an increase to 44% of the East Greenland-Svalbard-Barents stock being categorised as sexually mature. These results show the important information that may be derived from historical whaling records. Since the commercial hunt of the bowheads ceased in the European Arctic there have been substantial changes in both the oceanographic and sea ice regime in the region, thus understanding the past through whaling records can help to understand the implications of future climate-induced changes in bowhead whale populations and their habitat.